Development and characterization of dendritic cell internalization and activation assays contributing to the immunogenicity risk evaluation of biotherapeutics - Siegel, Michel; Padamsey, Aman; Bolender, Anna-Lena; Hargreaves, Patrick; Fraidling, Johannes; Ducret, Axel; Hartman, Katharina; Looney, Cary M.; Bertinetti-Lapatki, Cristina; Rohr, Olivier; Hickling, Timothy P.; Kraft, Thomas E.; et al. (Frontiers in Immunology, 2024)
Assessing immunogenicity risks during the development of biotherapeutics is crucial. Given the complexity of immunogenicity - influenced by myriad biological, immunological, and patient-specific factors - Individual risk assessments are poorly predictive, necessitating a holistic approach to immunogenicity risk assessment. Anti-drug antibody production starts with the internalization of drugs by antigen presenting cells such as dendritic cells, which present drug-derived peptides to CD4+ T cells as peptide-MHC-II complexes. Assessing dendritic cell function is common in preclinical immunogenicity risk assessments, including presentation of potential T cell epitopes using the MAPPs assay. However, other aspects of dendritic cell biology are often overlooked. To better understand the dendritic cell contribution to immunogenicity, we developed two flow cytometry-based assays: the dendritic cell internalization assay and the dendritic cell activation assay. Our assay addresses two issues with existing methods for measuring internalization into antigen presenting cells; lack of specificity for the cellular compartment of internalization or the recycling of internalized antibodies, and the increased risk of aggregation, when using a large payload for the detection of antibodies, that would lead to activation of irrelevant scavenger receptors in the context of dendritic cell internalization. We also developed a DC activation assay, improving on various aspects of its relevance for immunogenicity risk assessment compared to previously published protocols. Additionally, we identified DC-SIGN (CD209) and CD80 as crucial for understanding dendritic cell activation mechanisms leading to immunogenicity. To evaluate the performance of these two assays, we used a set of marketed therapeutic antibodies. The dendritic cell internalization assay revealed differences in internalization rates for marketed therapeutic antibodies, even those targeting the same antigen (e.g. PCSK9-targeting antibodies: bococizumab, evolocumab and alirocumab or TNF-targeting antibodies: adalimumab and infliximab), potentially accounting for differential immunogenicity liabilities. The DC activation assay also showed different patterns of DC activation between bococizumab, which rapidly accumulates within the lysosomes, and the other PCSK9-targeting antibodies (evolocumab and alirocumab), giving new insights into specific immunogenicity profiles. Overall, this study provides valuable information for future risk assessments of therapeutic antibodies in development.